Combined effects of low-molecular-weight organic acids on mobilization of arsenic and lead from multi-contaminated soils. (March 2017) - Onireti, Olaronke O.; Lin, Chuxia; Qin, Junhao
Abstract: A batch experiment was conducted to examine the combined effects of three common low-molecular-weight organic acids (LMWOAs) on the mobilization of arsenic and lead in different types of multi-contaminated soils. The capacity of individual LMWOAs (at a same molar concentration) to mobilize soil-borne As and Pb varied significantly. The combination of the organic acids did not make a marked "additive" effect on the mobilization of the investigated three elements. An "antagonistic" effect on element mobilization was clear in the treatments involving oxalic acid for some soils. The acid strength of a LMWOA did not play an important role in controlling the mobilization of elements. While the mobilization of As and Pb was closely associated with the dissolution of soil-borne Fe, soil properties such as original soil pH, organic matter contents and the total amount of the element relative to the total Fe markedly complicated the mobility of that element. Aging led to continual consumption of proton introduced from addition of LMWOAs and consequently caused dramatic changes in solution-borne Fe, which in turn resulted in change in As and Pb in the soil solution though different elements behaved differently. Highlights: Low-molecular-weight organic acids (LMWOAs) are reactive constitutes in root exudates. LMWOAs drive mobilization of soil-borne potentially toxic trace elements (PTTEs). Batch experiment to examine the combined effects of LMWOAs on mobility of PTTEs. Important insights into the complication of multiple LMWOAs on PTTEs were gained. Implications for better understanding mobility of PTTEs by LMWOAs in field.